Dinamika dan Tantangan dalam Pendidikan Pancasila di Era Globalisasi: Tinjauan Literatur - Mihit, Yohanes (PT Literasi Nusantara Publisher, 2023)
This article discusses the dynamics and challenges of Pancasila Education in the Era of Globalization. The data collection method was conducted through literature exploration using a literature review approach. The main focus was on the role of Pancasila education in facing various challenges. The data collection process consisted of searching relevant sources, determining subsections, examining references, extracting key points, and providing a comprehensive exposition of subsections. Pancasila education is not only an ideology but also the identity and foundation of the nation. In the era of globalization, where technology plays a significant role, wise digital literacy must be instilled in Pancasila education. The success of this education is measured in terms of cognitive, affective, and behavioural aspects. The younger generation must be able to apply the values of Pancasila in their daily lives. The involvement of families, educators, the government, and society as a whole is necessary for the success of Pancasila Education. With this approach, the young generation of Indonesia will be prepared to face changes, build unity, and uphold the nation's integrity amidst global dynamics. The importance of maintaining unity in diversity and promoting the values of Pancasila in community life is also highlighted in this article.